2009
DOI: 10.5039/agraria.v4i3a7
|View full text |Cite
|
Sign up to set email alerts
|

Nodulação natural de leguminosas em solos de cerrado do estado do Piauí

Abstract: O objetivo deste trabalho foi avaliar a ocorrência de nodulação natural em leguminosas por bactérias nodulíferas fixadoras de nitrogênio nativas do solo do Cerrado do Piauí. A capacidade de nodulação foi observada em feijão-caupi (Vigna unguiculata), leucena (Leucaena leucocephala), bordão-de-velho (Albizia sp.) e caneleiro (Cenostigma macrophyllum) semeadas em solos de Cerrado com diferentes manejos: Eucalipto plantado em 2006 (E6); Eucalipto plantado em 2007 (E7); Arroz em sistema convencional (AR); mata nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Similar results were reported by Souza et al, (2007) found that less root development of leucaena, which shows greater difficulty in establishing this species in soils of forest areas. The development of roots of leucaena is sensitive to soil acidity and the aluminum content, as noted by Vale et al, (1996) and Silva et al, (2009), which may explain the poor development of roots, a characteristic found for samples of forest soil used in the experiment. In both species were observed nodulation in all soils of the areas studied, with the best nodule formation in these species occurring in soil cultivation 1 and 4.…”
Section: Resultsmentioning
confidence: 66%
“…Similar results were reported by Souza et al, (2007) found that less root development of leucaena, which shows greater difficulty in establishing this species in soils of forest areas. The development of roots of leucaena is sensitive to soil acidity and the aluminum content, as noted by Vale et al, (1996) and Silva et al, (2009), which may explain the poor development of roots, a characteristic found for samples of forest soil used in the experiment. In both species were observed nodulation in all soils of the areas studied, with the best nodule formation in these species occurring in soil cultivation 1 and 4.…”
Section: Resultsmentioning
confidence: 66%
“…The results of nodulation contrasted with data from other studies that compared the ability of two legume nodulation (Souza et al, 2007), since in the present study, there was a higher nodulation of leucaena. The species showed high specificity to the microsymbionts (Silva et al, 2009) and this fact may be related to native rhizobial populations prevailing in the areas and the ability of these native rhizobia to establish effective symbiotic associations.…”
Section: Resultsmentioning
confidence: 98%
“…Jesus et al (2014) também verificaram, em estudo conduzido no Sudoeste do Piauí, relação direta entre a fertilidade do solo e nodulação em mudas de tamboril, sendo esta superior em solos de maior fertilidade. Resultados semelhantes foram reportados por Silva et al (2009), em experimento com as leguminosas leucena, bordão-de-velho e feijão-caupi cultivadas em solos de Cerrado sob diferentes sistemas…”
Section: Resultsunclassified
“…A. de Jesus et al capacidade nodulífera das espécies de leguminosas arbóreas é importante sob o ponto de vista ecológico e econômico, sendo objetivo de muitos estudos (Souza et al, 2007;Silva et al, 2009;Jesus et al, 2014).…”
Section: Growth and Nodulation Of Enterolobium Contortisiliquum Grownunclassified